2007
DOI: 10.1161/circulationaha.106.671545
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Microvascular Function in the Infarct-Related Artery by Intracoronary Transplantation of Bone Marrow Progenitor Cells in Patients With Acute Myocardial Infarction

Abstract: Background— The Doppler Substudy of the randomized, double-blind, placebo-controlled Reinfusion of Enriched Progenitor Cells and Infarct Remodeling in Acute Myocardial Infarction (REPAIR-AMI) trial aimed to investigate the effects of intracoronary infusion of bone marrow–derived progenitor cells (BMCs) on coronary blood flow regulation in patients with reperfused acute myocardial infarction. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(91 citation statements)
references
References 51 publications
1
89
0
1
Order By: Relevance
“…The potential mechanism is not well documented in previous studies. Recent studies suggested that BMSC infused into the coronary circulation at 4 to 7 days post-AMI reconstituted the damaged endothelium and promoted neovascularization, 22 which increased coronary flow reserve in the infarct-related artery. The improved perfusion capacity might stimulate the endothelium to release nitric oxide, which exerted antiatherosclerotic functions and might counteract the process of restenosis development and atherosclerotic disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanism is not well documented in previous studies. Recent studies suggested that BMSC infused into the coronary circulation at 4 to 7 days post-AMI reconstituted the damaged endothelium and promoted neovascularization, 22 which increased coronary flow reserve in the infarct-related artery. The improved perfusion capacity might stimulate the endothelium to release nitric oxide, which exerted antiatherosclerotic functions and might counteract the process of restenosis development and atherosclerotic disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Angiography has also been used to estimate microvascular function and microvascular growth. 176,177 A limitation of this approach is that only measurements of vasodilator reserve are obtained, not measurements of volume flow. Vasodilator reserve can be affected by downstream angiogenesis and influenced by the basal tone of the vasculature.…”
Section: Evaluation Of Microvascular Function Perfusion and Angiogementioning
confidence: 99%
“…6,25) Based on this evidence, larger trials have confirmed that intracoronary injection of autologous BMC is safe and potentially effective. 26) The beneficial effects of cell therapy in the setting of ischemic heart disease are not fully understood, and proposed mechanisms of action have included cardiomyocyte regeneration, 3,5,22) angiogenesis, [3][4][5]16,21,22,25) and inhibition of myocardial apoptosis and ventricular remodeling through paracrine factors of the infused cells. 3,14,21) The capacity of BMC to regenerate myocytes has been a matter of intense debate to date.…”
Section: Discussionmentioning
confidence: 95%